Effect of the fluorine substitution for oxygen in the heavily Pb-doped Bi-2212 phase of (Bi, Pb)2(Sr, Ba)2CaCu2O8. Issue 1 (July 2021) - Ito, R; Kawamata, T; Noji, T; Kato, M
Abstract: Polycrystalline samples of the Bi-2212 phase of Bi2− x Pb x Sr2 CaCu2 O8− z F z with x (Pb) = 0.6 and 1.0 have been prepared. All the samples are almost of the single phase with the Bi-2212 structure for x (Pb) = 0.6. The value of Tc ∼ 82 K for z (F) = 0 increases up to 86–88 K for z (F) = 0.2–0.6. This may be due to the decrease in the amount of vacancy at the O-site by the introduction of F − . In addition, we have successfully synthesized the partially Ba-substituted Bi-2212 phase of Bi1.4 Pb0.6 Sr2− y Ba y CaCu2 O7.8 F0.2 with 0 ≤ y (Ba) ≤ 0.5. Tc increases up to 98 K for y (Ba) = 0.5. The enhancement of Tc through the Ba-substitution may be due to the increase in the distance between Cu and the apical oxygen.